Highly Efficient Genome Editing in Plant Protoplasts by Ribonucleoprotein Delivery of CRISPR-Cas12a Nucleases - Zhang, Yingxiao; Cheng, Yanhao; Fang, Hong; Roberts, Nathaniel; Zhang, Liyang; Vakulskas, Christopher A.; Niedz, Randall P.; Culver, James N.; Qi, Yiping (Frontiers in Genome Editing, 2022)
Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) mediated genome editing is a powerful approach for crop augmentations. Traditional transformation methods based on plasmid delivery pose concerns associated with transgene integration and off-target effects. CRISPR delivered as ribonucleoproteins (RNPs) can prevent exogenous DNA integration, minimize off-target effects, and reduce cellular toxicity. Although RNP delivered CRISPR genome editing has been demonstrated in many plant species, optimization strategies that yield high editing efficiencies have not been thoroughly investigated. Using rice and citrus protoplast systems we demonstrated highly efficient genome editing using Cas12a delivered as RNPs. Four Cas12a variants, including LbCas12a, LbCas12a-E795L, AsCas12a and AsCas12a Ultra, were investigated. Nearly 100% editing efficiency was observed for three out of four target sites by LbCas12a, LbCas12a-E795L and AsCas12a Ultra, as measured by restriction fragment length polymorphism (RFLP) and verified by next generation sequencing of PCR amplicons. RNP delivery resulted in higher editing efficiencies than plasmid delivery at 32℃ and 25℃. LbCas12a and LbCas12a-E795L demonstrated increased editing efficiencies in comparison to AsCas12a and AsCas12a Ultra, especially when used at lower RNP concentrations. In addition, we discovered that a 1:1 Cas12a:crRNA molar ratio is sufficient to achieve efficient genome editing. Nuclear localization signals (NLSs) are essential for efficient RNP-based genome editing. However, the different crRNA modifications tested did not significantly improve genome editing efficiency. Finally, we applied the Cas12a RNP system in citrus protoplasts and obtained similarly high editing efficiencies at the target site. Our study provides a comprehensive guideline for Cas12a-mediated genome editing using RNP delivery in plant cells, setting the foundation for the generation of transgene-free genome edited plants.